Political activities of the Carpathian Germans in the interwar period = Działalność polityczna Niemców karpackich w okresie dwudziestolecia międzywojennego - Żarna, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the interwar period, Czechoslovakia was the multiethnic state. The most numerous minority in Czechoslovakia were Germans. They presented over 20% of all First Republic population. The majority of this ethnic group inhabited in western part of Germany - they were called "Sudeten Germans". Carpathian Germans inhabit the fields of Slovakia and Carpathian Ruthenia. They were less numerous, diffuse and less organized. In analyzed period in Slovakia rivaled two biggest German political parties: the Zipser German Party and the Carpathian Germans Party. About influences among local Germans tried also Hungarians. Finally has won the Carpathian Germans Party, around which has come the consolidation of Slovak German. It was subordinated Sudeten Germans Party and realized the interests of the Nazi Germany.
Keywords: Nazi Germany; Carpathian Germans; Carpathian Germans Party; Zipser German Party; German minority; nazistowskie Niemcy; Niemcy karpaccy; Partia Niemców Karpackich; Partia Niemców Spiskich; mniejszość niemiecka